Effects of computer-based testing on test performance and testing motivation - Chua, Y.P. (Elsevier, 2012)
Computer-based testing (CBT) is a green computing strategies used to reduce paper consumption. However, some scholars have questioned the effectiveness of CBT and suggested for conducting systematic studies on CBT to carefully check its reliability and validity before opting for it. Recently, some studies have evaluated the effectiveness of CBT by comparing it with paper-pencil testing (PPT), and the findings were inconsistent. Besides this, most of these studies have been conducted using quasi or basic experimental designs without identifying testing effects on test takers. The limitation of these design is testing effects might occur when a participant in the control or treatment group is tested at least twice on a same test, and it influences the outcomes of taking a posttest, therefore, the findings might be misinterpreted. This study employed a Solomon four-group experimental design (2x3 factorial design) on a group of student teachers (n=140) to compare CBT and PPT on test performance (test scores), testing time and testing motivation. Results indicated that the CBT mode is more reliable in terms of internal and external validity. The CBT significantly reduced testing time and developed stronger self-efficacy, intrinsic and social testing motivation in the participants.